Astronomy in India : a historical perspective - Padmanabhan, T. (Thanu), 1957-; Indian National Science Academy (2010)
Contributed essays.
"Indian National Science Academy Platinum Jubilee special volume."
Includes bibliographical references (pages 143-145).